Scalable wideband equivalent circuit model for silicon-based on-chip transmission lines*Project supported by National Natural Science Foundation of China (No. 61674036). (June 2017) - Wang, Hansheng; He, Weiliang; Zhang, Minghui; Tanh, Lu
Abstract: A scalable wideband equivalent circuit model of silicon-based on-chip transmission lines is presented in this paper along with an efficient analytical parameter extraction method based on improved characteristic function approach, including a relevant equation to reduce the deviation caused by approximation. The model consists of both series and shunt lumped elements and accounts for high-order parasitic effects. The equivalent circuit model is derived and verified to recover the frequency-dependent parameters at a range from direct current to 50 GHz accurately. The scalability of the model is proved by comparing simulated and measured scattering parameters with the method of cascade, attaining excellent results based on samples made from CMOS 0.13 and 0.18 μm process.